Tempo, path dependence e instabilidade : as convergências entre Keynes e Sraffa - Mandarino, Gabriel Vieira (2012)
This dissertation analyses some congruent topics in the theories of Keynes and Sraffa. It studies the question of time in the economic theory and that related to the path dependence in the neoclassical economics. It also studies the problem related to the production prices and the conditions necessary for them to work as centers of gravity. Using the General Theory, it examines one kind of path dependence, related to the influence of the short run expectations upon the long run expectations. Moreover, it analyses how the post-keynesian theory treat questions related to the endogenous economic growth and the economic instability. For these purposes, it studies authors such as Harrod, Kregel and Setterfield. The dissertation also shows that is it not possible to formulate a model with an equilibrium position in the long run. That fact results in an unstable economic process, in opposition to the stability in the economic growth model of Solow. Finally, it studies questions related to the nature of capital.